PENGARUH WFH, MOTIVASI, DAN PENGETAHUAN INVESTOR RITEL TERHADAP MINAT INVESTASI - Eka Purnama; Hasim As’ari (Value : Jurnal Manajemen dan Akuntansi, 2023)
Retail investors, although relatively small investment funds, have a very important impact on the dynamics of the capital market. New challenges arising from the Covid-19 pandemic, such as market fluctuations and changes in lifestyle due to work from home policies, add complexity to the investment environment. The purpose of this study is to investigate the impact of work from home, motivation, and investment knowledge on retail investor interest in the capital market, with reference to the Theory of Planned Behavior (TPB). This study used a quantitative approach using survey methods. The Purposive Sampling technique was used to analyze the hypothesis, involving the distribution of questionnaires to 80 respondents who were employee class students of the Faculty of Economics, Mercu Buana University, Yogyakarta, batch 2019-2022. The collected data was analyzed using SPSS Statistics 25. The test results show that work from home, motivation, and investment knowledge have a significant positive impact on retail investors' interest in the capital market. These findings provide valuable insights to understand the dynamics of retail investor behavior in the face of changing investment environments, especially in the era of work from home policy adaptation. Keywords: WFH, Motivation, Knowledge, Investment, Capital Markets